Career Development in Children (Childhood): Literature Review - Heppi Sasmita Aprinal; A Muri Yusuf; Mega Iswari; Afdal Afdal (Bisma The Journal of Counseling, 2021)
Career development is one of the long developments in the life span experienced by individuals that lead to self-actualization as the pinnacle of successful career development. Career involves the stages of individual development in achieving and completing from one stage to the next. The success of completing developmental tasks from existing developmental stages determines the individual's success in fulfilling developmental tasks at higher stages. Therefore, career guidance is very much needed in childhood so that the career path is more focused and in this case, of course, the counseling guidance teacher plays an important role in directing and mentoring students who are in such an educational institution.